2014
DOI: 10.1021/jo501177g
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Three or Two Distal Double Bonds at the Methylene Bridges of the Calix[4]arene Scaffold

Abstract: Partial oxidation of the 1,3-alternate atropisomer of p-tert-butylcalix[4]arene tetraacetate with CrO3 afforded mainly a mixture of trioxo- and tetraoxo-calix[4]arene tetraacetate derivatives. The trioxotetrahydroxy derivative 6 was isolated from the mixture after hydrolysis of the crude product, followed by trituration with ethanol. Trioxocalix[4]arene adopts in the crystal a 1,2-alternate conformation. Acetylation or alkylation of the tetrahydroxytrioxocalix[4]arene 6 with acetic anhydride and 1-bromobutane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…On these grounds, it can be concluded that in contrast to the parent 6a , the alkylation of 5 with this reagent proceeds with high stereoselectivity and affords a single atropisomeric product. A similar stereoselective butylation was recently observed in a calix[4]arene derivative possessing three oxo groups at the bridges 9b. The simplicity of the NMR pattern of the product is consistent with either a cone or an 1,3‐alternate form.…”
Section: Resultssupporting
confidence: 78%
“…On these grounds, it can be concluded that in contrast to the parent 6a , the alkylation of 5 with this reagent proceeds with high stereoselectivity and affords a single atropisomeric product. A similar stereoselective butylation was recently observed in a calix[4]arene derivative possessing three oxo groups at the bridges 9b. The simplicity of the NMR pattern of the product is consistent with either a cone or an 1,3‐alternate form.…”
Section: Resultssupporting
confidence: 78%
“…We recently described the preparation of calixradialenes, that is, calix[ n ]arenes possessing exocyclic double bonds at all the bridges (e.g., 3 , 4 ) as well as calix[4]arene derivatives possessing two or three exocyclic double bonds . A key step in the introduction of the double bonds involved the reaction of keto‐calixarenes with MeLi, followed by acid‐catalyzed dehydration of the isomeric mixture of addition products.…”
Section: Resultsmentioning
confidence: 99%
“…Calixarene 17 displays in the 1 HNMR spectrum as ignal at d = 5.41 ppm characteristic of the vinyl protons of the exocyclic double bonds in calixradialenes. [15] Calixarene 17 was treated with dichlorocarbene and the CÀ Cl bonds of the crude product were reduced with sodium in tBuOH/THF to afford the target product 18 [Eq.…”
Section: Calix[6]arene Derivative With Two Distal Spirocyclopropyl Grmentioning
confidence: 99%
“…Calixarenes possessing a pair of carbonyl and bromomethylene bridges ( 4 and 5 , Scheme ) were obtained via photochemical bromination of 1a with 6.3 equivalents of NBS followed by hydrolysis of the resulting hexabromo derivatives. These compounds proved to be useful stating materials for the preparation of calix[4]arenes with two different modification of the methylene bridges . Here we describe the preparation of a larger analog of 4 , i.e., a calix[6]arene derivative possessing both a pair of distal carbonyl groups and four monobrominated bridges.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds proved to be useful stating materials for the preparation of calix [4]arenes with two different modification of the methylene bridges. [12][13][14] Here we describe the preparation of a larger analog of 4, i.e., a calix [6]arene derivative possessing both a pair of distal carbonyl groups and four monobrominated bridges. Scheme 2.…”
mentioning
confidence: 99%